Economic evaluation model for the energy Demand Response. (1st October 2016) - Fera, M.; Macchiaroli, R.; Iannone, R.; Miranda, S.; Riemma, S.
Abstract: The need for new solutions for the generation, transmission, and distribution of electricity has become apparent with advancements of technology worldwide. This disposition has been revealed by the deregulation of the electricity market, the technological processes in constant evolution, the focus on environmental problems, and the need to manage and protect energy loads that are more sensitive to disturbances in the grid. Numerous significant research and development efforts, involving a large number of technology areas and requiring a highly interdisciplinary design vision, have led to the emergence of a new concept called "Smart Grids." In this context, attention is emphasized toward the Demand Response (DR), a particular tactic for the intelligent management of users' electrical loads. This paper aims to present an algorithm that helps the aggregator of energy loads in carrying out its daily decisions, using an economic objective function. A mathematical model for this goal was developed, and a heuristic solution was used to calculate the configuration of load distributions. Conclusively, the model was tested to understand its effectiveness and to determine the capability of an aggregator to have revenues from the application of a DR tactic. Highlights: Demand Response management model. Economic management model. Demand Response for service companies.